2020
DOI: 10.1002/1873-3468.13973
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin deficiency in Barth syndrome is not associated with increased superoxide/H2O2 production in heart and skeletal muscle mitochondria

Abstract: Barth syndrome (BTHS) is a rare X-linked genetic disorder caused by mutations in the gene encoding the transacylase tafazzin and characterized by loss of cardiolipin and severe cardiomyopathy. Mitochondrial oxidants have been implicated in the cardiomyopathy in BTHS. Eleven mitochondrial sites produce superoxide/hydrogen peroxide (H 2 O 2) at significant rates. Which of these sites generate oxidants at excessive rates in BTHS is unknown. Here, we measured the maximum capacity of superoxide/H 2 O 2 production f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 67 publications
(178 reference statements)
4
23
3
Order By: Relevance
“…Slowed contractile kinetics in TazKD soleus compared to WT did not translate to changes in grip strength. A lack of change to in vivo muscle function is similar to previous research in that locomotor activity in TazKD mice did not differ from WT ( Cole et al, 2018 ; Goncalves et al, 2021 ). Grip strength is a common non-invasive in vivo evaluation of muscle force ( Ge et al, 2016 ; Martinez-Huenchullan et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Slowed contractile kinetics in TazKD soleus compared to WT did not translate to changes in grip strength. A lack of change to in vivo muscle function is similar to previous research in that locomotor activity in TazKD mice did not differ from WT ( Cole et al, 2018 ; Goncalves et al, 2021 ). Grip strength is a common non-invasive in vivo evaluation of muscle force ( Ge et al, 2016 ; Martinez-Huenchullan et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, this is the first study to fully characterize an impaired contractile phenotype in the pre-clinical rodent model of Barth syndrome and the potential efficacy of dietary supplemental LA to reverse this phenotype. Similar to previous studies, administration of doxycycline to TazKD mice in utero and post-weaning resulted in decreased skeletal muscle Taz mRNA, protein, CL content, CL 18:2n6 composition, and increased MLCL:CL ratio ( Acehan et al, 2011 ; Soustek et al, 2011 ; Ikon et al, 2018 ; Johnson et al, 2018 ; Goncalves et al, 2021 ), along with reduced weight gain ( Acehan et al, 2011 ; Cole et al, 2016 ; Ikon et al, 2018 ; Johnson et al, 2018 ; Goncalves et al, 2021 ). The main findings are (1) TazKD soleus demonstrated slower force development and relaxation in vitro as key contributors to this impaired contractile phenotype, (2) the impaired contractile phenotype seen in vitro in TazKD compared to WT did not translate to altered muscle function in vivo , and (3) supplemental LA attenuated, to some degree, soleus in vitro impaired contractile phenotype in TazKD mice, which appears to not be fully mediated by CL content and composition.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These substrate and inhibitor combinations have been successfully used to demonstrate /H 2 O 2 sources outside of complex I and II can also generate significant amounts of ROS [ 34 , 56 ]. These approaches have been implemented to study ROS production in various disease models including Barth's syndrome, heart disease, insulin resistance, and diet-induced obesity [ 27 , [56] , [57] , [58] ]. Additionally, this toolkit was used to show there are sex and mouse-strain differences in the native rates of production for the twelve sites [ 56 , 59 ].…”
Section: The Methodological Toolkit For Interrogating Individual Rates Of Ros Productionmentioning
confidence: 99%
“…In contrast to these findings, a recent investigation showed that ROS levels were indistinguishable between TAZ knock-down mice and wild-type littermates. Thus, it can be concluded that cardiolipin deficiency in Barth syndrome pathogenesis is unlikely associated with boosted production of ROS [ 152 ].…”
Section: Mitochondrial Dysfunction In Specific Neuromuscular Disordersmentioning
confidence: 99%